2011
DOI: 10.1016/j.vaccine.2011.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is associated with impairment of vaccine-induced antibody response and increase in post-vaccination influenza infection in community-dwelling older adults

Abstract: Annual immunization with a trivalent inactivated vaccine (TIV) is considered efficacious for prevention of seasonal influenza in older adults. However, significant controversy exists in the current literature regarding the clinical effectiveness of TIV immunization in this highly heterogeneous population. Frailty is an important geriatric syndrome characterized by decreased physiologic reserve and increased vulnerability to stressors. Using a validated set of frailty criteria, we conducted a prospective observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
114
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 40 publications
2
114
3
3
Order By: Relevance
“…13 This study benefitted from a high degree of similarity among the study groups, effectively controlling for a range of potential influences on responses to vaccination including age, 19 sex, prior influenza vaccination, 15,16 frailty, 20 chronic health conditions, obesity, 21 moderate exercise 22 and probiotic use. 23 Similarity of baseline antibody titers among the study groups avoided the need for adjustment of observed responses.…”
Section: Discussionmentioning
confidence: 99%
“…13 This study benefitted from a high degree of similarity among the study groups, effectively controlling for a range of potential influences on responses to vaccination including age, 19 sex, prior influenza vaccination, 15,16 frailty, 20 chronic health conditions, obesity, 21 moderate exercise 22 and probiotic use. 23 Similarity of baseline antibody titers among the study groups avoided the need for adjustment of observed responses.…”
Section: Discussionmentioning
confidence: 99%
“…Sampai penelitian ini selesai dilakukan, peneliti belum menemukan penelitian lain yang khusus melaporkan hubungan status frailty dengan imunogenesitas vaksin secara langsung, selain penelitian dari Yao, dkk. 10 Pada penelitian ini, juga dilakukan penilaian risiko relatif terhadap keluaran yang diamati yaitu kejadian tidak serokonversi. Dari hasil perhitungan, didapatkan risiko kejadian tidak serokonversi pada kelompok pre-frail/frail adalah relatif sama jika dibandingkan dengan kelompok yang sehat.…”
Section: Hubungan Status Frailty Dengan Serokonversi Dan Seroproteksiunclassified
“…Hal ini sesuai dengan tingkat seroproteksi yang dicapai pada penelitian Yao, dkk. 10 Tidak ada perbedaan bermakna antara tingkat seroproteksi juga antar kelompok berdasarkan status frailty. Eijndhoven, dkk.…”
Section: Hubungan Status Frailty Dengan Serokonversi Dan Seroproteksiunclassified
“…This mainly depends on the vaccines immune system capacities and some people simply does not respond adequately or at all [3,4]. For example, older adults are commonly described to fail to respond proprely to antigenic stimuli compared to their younger counterparts [3].…”
mentioning
confidence: 99%
“…For example, older adults are commonly described to fail to respond proprely to antigenic stimuli compared to their younger counterparts [3]. Although the immunosenescence process greatly contributes to this less-than optimal immune response to vaccination this decline is however not uniform within this population [5], frailer individuals demonstrating the poorer responses [4]. While the exact benefit of vaccination in the global aged population is still widely debated, the overall body of evidence nevertheless suggests that vaccination is however beneficial [2].…”
mentioning
confidence: 99%